Quantitative Analysis of Caffeine in Roasted Coffee: A Comparison of Brewing Methods - Iwona Mystkowska; Aleksandra Dmitrowicz; Monika Sijko-Szpańska (Applied Sciences)
Coffee is one of the most widely consumed beverages in the world due to its sensory and health benefits. The caffeine content, a bioactive compound of coffee, depends on many factors, including the brewing method, which is the subject of ongoing scientific research. In addition, various methods are used in studies to determine the caffeine content. However, it is worth noting that there is considerable variation in the individual analytical parameters within these methods. The aim of this study was to update the data on the effects of different brewing methods on the caffeine content of the brew and to present the current state of knowledge on techniques for the determination of this compound. A literature review was conducted, taking into account the latest studies in this field. The results showed that the caffeine content (mg/100 mL) of the brew prepared with the Cold Brew method was 48.50–179.95, Espresso—50.40–965.60, French Press—52.00–123.90, AeroPress—56.35–120.92, and Moka—128.00–539.90. These methods were characterized by different brewing parameters (time, water temperature and pressure, ratio of coffee to water), which differentiated the caffeine content. In addition, some methods were characterized by a wide range of caffeine content, suggesting that even minor variations in brewing method parameters may affect the content of this ingredient. High-performance liquid chromatography (HPLC) was the predominant method used. The detector wavelengths, along with other parameters of the HPLC method, such as gradient profiles and column temperatures, can affect the precision and accuracy of the analysis, and these differences can modify analyte retention and detection, leading to discrepancies in results. These results point to the need for studies that consider various brewing methods and a wide range of coffee types, including roast and origin, to accurately determine the effects of these factors on caffeine content determined by one precise method.